Marketing Strategy of Tape Producers in Pematang Panjang Village - Nurkamilah Nurkamilah; Syaharuddin Syaharuddin; Raihanah Sari; Syarifuddin Syarifuddin; Fatwa Nur'aini (The Innovation of Social Studies Journal, 2024)
he aim of this research is to 1) Describe product strategies for marketing Tape. 2) Describe the pricing strategy for marketing Tape. 3) Describe the marketing strategy for Tape. 4) Describe promotional strategies for marketing Tape. This research was conducted using a qualitative approach with descriptive methods used in this research to describe the marketing strategy of Tape producers in Pematang Panjang Village. The subjects in this research were Tape craftsmen. The data collection technique was carried out by observing the location of the peat Tape craftsmen in Pematang Panjang, interviews and documentation in the form of recordings and pictures. Data analysis uses data reduction based on research objectives, presenting data based on descriptions and drawing conclusions. Test data validity and triangulation. As a result of the research, the concept used in the marketing mix for Tape is the 4P model because it is good enough so that the effectiveness of the four models can increase and continue to grow in marketing, especially the number of consumers. The marketing mix concept is used as a concept that develops a strategy which will later become a benchmark for the company in marketing so that it will get the desired target.